Water-energy-emissions nexus – an integrated analysis applied to a case study - Barrouin Melo, Leonardo; Lombardi Costa, Antonella; Estanislau, Fidellis; Eduardo Velasquez, Carlos; Fortini, Angela; Nikolaus Pinto Moura, Gustavo (International Journal of Sustainable Energy Planning and Management, 2022)
Competition for water use, population growth, territorial expansion for housing, the finitude of fossil fuels, climate change, and the lack of consistent and continuous energy planning are some of the existing problems related to planning and monitoring energy supply systems. This work presents an integrated analysis of the water-energy-emissions nexus using two computational models simultaneously in order to consider a case study for the modeling of hydropower plants. The main results include the reduction in hydropower generation at the end of the study horizon (2019 – 2049) between (-16.8%) and (-7.8%) considering water restriction scenarios. Final electricity demand, in the reference scenario, increased 40.8% and, in alternative scenarios, there was an increase between 63.6% and 89.5% when reductions in the rainfall regime were considered.